Determinants Of Financial Performance To Stock Return - Devita, Hety; Arviana, Nerissa (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aims to examine the effect of return on assets (X1), return on equity (X2), and earnings per share (X3) on stock returns (Y) in automotive sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2016-2021 period.The population used in this study is a manufacturing company in the automotive sub-sector. This study uses saturated sampling (Census) with a total sample of 7 companies.The data analysis technique in this study uses descriptive analysis, classical assumption analysis, multiple linear regression analysis, with hypothesis testing using -t test and F test.The results of the study show that: (1) partially the return on asset (X1) variable has a positive and significant effect on stock returns. (2) partially the return on equity variable (X2) has a negative and significant effect on stock returns. (3) partially the earning per share (X3) variable has no positive and insignificant effect on stock returns. (4) Simultaneously, the return on assets (X1), return on equity (X2) and earnings per share (X3) variables have a positive and significant effect on stock returns.